Factors associated with attitude towards the elderly among medical and nursing students in a Malaysian Public University - Damulak, Panmial Priscilla (2016)
Introduction: The improvement in healthcare services and life expectancy, and also decrease in fertility rate, leads to an exponential increase in elderly population. The attitude of healthcare workers has to change with this increase as they will be encountering more aged clients in future. Research has shown that health care workers and undergraduate health care students have negatively preconceived ideas about the elderly leading to unfavourable attitude towards them. Aims and objectives: To determine the factors associated with attitude towards the elderly among Medical and Nursing students in Universiti Putra Malaysia. Method: A cross-sectional study was carried out using proportional stratified sampling, involving 456 medical students and 63 nursing students. The selection of the respondents was done by simple random sampling method using guided self-administered questionnaire distributed to year 1 to year 5 medical students and year 1 to year 3 nursing students from the Faculty of Medicine and Health Sciences, Universiti Putra Malaysia. The questionnaire was pre-tested and validated prior to its use and consisted of 6 sections; socio-demographic characteristics, modified Kogan‘s Attitude Towards Old People Scale (ATOP), modified Facts on Ageing Quiz 2 (FAQ2), modified filial responsibility questionnaire, experience of living with elderly questions as well as questions on exposure to geriatric module. Three level of analyses were conducted which are descriptive analysis, chi-square and logistic regression. The significance level was set at 0.05. Results: A total of 519 respondents were involved in the study with 91.4% response rate. It was observed that 52.0% of the respondents had negative attitude towards the elderly, 70.3% had good knowledge of ageing, only 29.7% were currently living with the elderly. Meanwhile 74.0% have ever lived with the elderly, 53.0% had low perceived filial responsibility, and 54.1% had no exposure to geriatric module. There were significant associations between attitude towards elderly people and year of study (X2=12.699, p= 0.013), and also perceived filial responsibility X2 =44.599, p = 0.001). However, only perceived filial responsibility was the significant predicting factor for attitude towards the elderly (AOR=2.957, p = 0.001, 95% CI=1.999-4.372), in which those with high perceived filial responsibility had 3 times higher odds of having positive attitude towards the elderly than those who had low perceived filial responsibility However, the model only explains 12.4% of the variation in positive attitude towards the elderly (Negelkerke‘s R2 = 0.124) Conclusion: The findings of the study revealed that slightly more than half of the medical and nursing students in Universiti Putra Malaysia have negative attitude towards the elderly and perceived filial responsibility is the only predictor of attitude towards the elderly. In view of the upsurge in elderly population and an important role play by the healthcare workers in the care of elderly people, it is suggested that the importance of filial responsibility be more emphasized and embedded in the geriatric curriculum of medical and nursing students at every stage of their training. Keywords: attitude, knowledge of ageing, perceived filial responsibility, exposure to geriatric module, elderly.